FAKTOR RISIKO KEJADIAN KANKER PAYUDARA - Anitasari, Bestfy; Marthakoesoemah, Meitha Roosmeilany; Noorma, Nilam; Herniyatun, Herniyatun; Wahidah, Nurul Jannatul (Ensiklopedia of Journal, 2024)
Breast cancer is a biological disease that can arise in breast tissue, with symptoms of uncontrolled cell division and maturation. Breast cancer is the fifth most common cause of death worldwide, in Indonesia breast cancer ranks first among all types of cancer. The purpose of the study was to determine the factors associated with the incidence of breast cancer in outpatients at PKU Muhammadiyah Gombong Hospital. This type of research is quantitative with cross sectional research design. The sample consisted of 108 respondents who were taken using purposive sampling technique. Instrument or measuring tool used in this study was a questionnaire. The results showed that there was a relationship between age (p value: 0.009) and duration of contraceptive use (p value: 0.001) with the incidence of breast cancer. It is recommended, especially for women, to be active potential acceptors in choosing contraceptives and to be open enough in the process of determining contraceptives.